PENERAPAN KONSEP TRI HITA KARANA DALAM LINGKUNGAN PERMUKIMAN PERDESAAN (KASUS KABUPATEN BADUNG PROVINSI BALI) - Wesnawa, I Gede Astra (Bumi Lestari; Vol 10 No 2 (2010), 2010)
The research conducted in villages in Badung District due to their existence as safeguarder of adat and culture which indicate the changes in the implementation of Tri Hita Karana (THK) concept. It aimed at (1) identifying forms of change in the implementation of THK concept in village settlements in Badung, Bali Province, (2) identifying factors causing the change, (3) analyzing the process of change, and (4) studying the impact of change. In order to achieve its objectives, the research utilized a survey. The methods of sampling consist of: (1) areal sampling, which was based on landscape unit feature and administrative which were selected proportionally, and (2) subject sampling, which consists of the Head of the family determined through stratified sampling technique based on sosial stratification of triwangsa group and jabawangsa. The analysis was carried out using a qualitative technique supported by quantitative data on change in village settlements which were based upon the THK concept. The research results indicated that four elements have changed . First, forms of change in the implementation of THK concept in the mesoscale village settlements occured in the element of parhyangan, pawongan, and palemahan in mountainous and plains are relatively the same. The lay out are in the forms of trespassing the circle of holly areas and the placement of temple in vertical orientation. In microscale, the spatial function of biotic component and social culture is transformed into social and economic function for jabawangsa group, whereas triwangsa still maintains the existence of facilities, lay out, and spatial function on abiotic, biotic and social culture component. Second, factors causing the change in the mesoscale village settlement based on THK concept in mountainous and plains were the form of land exploitation, the vegetation availability, income, and the large of land ownership. Meanwhile, in microscale, the limit of land is the only factor. Third, the process of change in mountainous and plains both the mesoscale and microscale were evolutionary and revolutionary. Fourth, the impact of change existed in the mesoscale mountainous and plains were the decrease of preservation area [biotic] and spiritual degradation, whereas in microscale were decrease of space availability for social component [abiotic], donation pattern, and the transformation from primary to secondary and tertiary sector [social culture] on triwangsa and jabawangsa group. The THK concept as manifestation of local wisdom in village settlements is adaptive to changes and advancement of time as indicated by compromising the kahyangan tiga part as the soul of the settlement while the territory as the physical body of the village as well as the residents. Such a harmony will assure preservation of harmonious environment.
Keywords: THK implementation, change, impact, environment, village settlement